The Impact of Customer Mistreatment on Employee Displaced Aggression: The Moderating Effect of Interpersonal Sensitivity and Moral Identity - Fang Liu; Gang Chen; Yu Liu (Frontiers in Psychology, 2020)
Although customer mistreatment produces harmful consequences for employees and organizations, our understanding of the boundary conditions of customer mistreatment has largely been neglected. This study examines whether and when customer mistreatment influences employee displaced aggression toward coworkers by demonstrating interpersonal sensitivity and moral identity traits as two critical boundary conditions. Through the analysis of 623 employees’ questionnaire data, the results showed that customer mistreatment was positively related to employee displaced aggression toward coworkers. Furthermore, interpersonal sensitivity exacerbates the effect of customer mistreatment on displaced aggressive behaviors, while moral identity buffering the effect.